Advances in breast imaging: a review on where we are and where we are going - Coelho, Felipe Marcondes de Oliveira; Gontijo, Maria Fernanda Sperotto Valadares; Loaiza, Katty Paulina Cabrera; Franco, Renata Capanema Saliba; Avelar, José Tadeu Campos de (Mastology, 2024)
Breast radiology has undergone significant advances in recent years, and, naturally, several possibilities open up for attending physicians. Concomitantly, it increases the responsibility to keep up to date and provide the best care for each patient. Aware of the complex implications that the implementation of some of the technological advances may bring, such as increased costs, limited availability of equipment, and a potential increase in examination time, the objective of this study is to carry out a narrative review and provide a collection of advances that, in our opinion, are already gaining ground and should be consolidated in clinical practice. We will discuss new breast imaging methods that can be used both for screening and for the diagnostic investigation of breast lesions and we will summarize the most relevant aspects of each of them, addressing the technique, applicability, positive aspects, and limitations of each modality in a standardized way.